The use of virtual currencies in microtransactions as a predatory monetization tool - Tomić Nenad; Aleksić Dušan (Megatrend Revija)
Microtransactions increase the possibility of charging individual players an amount significantly higher than the average premium price of the complete game. A large number of publishers also use a special currency created solely for the purpose of paying microtransactions in that video game. Such currency is called virtual currency and as a rule it only works in a closed community formed around a specific video game. The topic of this paper is the use of virtual currencies in video games as a tool for performing microtransactions. The aim of the paper is to point out the negative aspects of this aggressive form of monetization in video games and to reveal approaches for avoiding it. Virtual currencies are the most refined tool of aggressive monetization, because their application is the easiest way to achieve the unfair practices, which makes publishers earn more money for the content offered. The key to the sustainable use of virtual currencies in video games is a balance between the efforts of gamers and publishers.